2000
DOI: 10.1007/s000110050629
|View full text |Cite
|
Sign up to set email alerts
|

Activated peritoneal macrophages inhibit the proliferation of rat ascites hepatoma AH-130 cells via the production of tumor necrosis factor- α and nitric oxide

Abstract: Together these observations suggest that when peritoneal macrophages are activated by LPS and IL-2, they suppress the proliferation of ascites hepatoma AH-130 cells via the production of TNF-alpha and nitric oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Maekawa et al [24] recently demonstrated that peritoneal macrophages activated by LPS and IL-2 suppressed the proliferation of ascites hepatoma AH-130 cells via the production of TNF-alpha and NO. It has been shown that eNOS-overexpressing endothelial cells significantly inhibited smooth muscle cells proliferation in vitro [25].…”
Section: Discussionmentioning
confidence: 97%
“…Maekawa et al [24] recently demonstrated that peritoneal macrophages activated by LPS and IL-2 suppressed the proliferation of ascites hepatoma AH-130 cells via the production of TNF-alpha and NO. It has been shown that eNOS-overexpressing endothelial cells significantly inhibited smooth muscle cells proliferation in vitro [25].…”
Section: Discussionmentioning
confidence: 97%
“…Macrophages produce cytokines such as TNF-a and IL-6 and free radicals such as superoxide and nitric oxide (NO) (Maekawa et al, 2000). As mentioned above, the jellyfish collagen stimulated the phagocytotic activity of J774.1 cells.…”
Section: Cells and P-macmentioning
confidence: 97%
“…Moreover, tumor cells inhibit the production of reactive oxygen intermediates by macrophages [22]. A rather inconsistent pattern emerges from the studies on the influence of tumor cells on NO release by the monocyte-macrophage lineage; stimulatory in the case of leukaemia, lymphoma, mastocytoma [23][24][25], ascites hepatoma [26], fibrosarcoma [27], and colon carcinoma cells [28,29]; inhibitory in the case of mammary carcinoma [30,31] and murine melanoma [32].…”
Section: Introductionmentioning
confidence: 98%